Strategies to improve patients' awareness regarding the patients' rights charter in selected hospitals of Limpopo Province, South Africa - Thema, Adolphina Mokgadi (My University, 2020)
Background Patient’s awareness of the patients’ rights charter was assessed as it was not known and strategies were developed to improve patients’ awareness in the selected hospitals of the Limpopo Province. Aim To assess, describe and explore patients’ awareness of their rights and to develop strategies to improve patients’ awareness of their rights. Study methodology A qualitative exploratory and descriptive research approach were used. Data were collected from 30 patients using semi-structured face-to-face interviews. Data were audiotaped and field notes were taken. The Turfloop Research Ethics Committee gave ethical clearance. The Department of Health permitted for the study to be conducted in the selected hospitals. Ethical considerations and measures to ensure trustworthiness were observed. Results Results showed that patients lacked awareness of the Patients’ Rights Charter and they could not give examples or name the rights they have as patients. The study revealed that sources of information regarding the Patients’ Rights were limited. Patients indicated that Patients’ Rights implementation was situational. Patients also experienced disrespect regarding their rights. In addition, strategies to improve patients’ awareness regarding the Patients’ Rights Charter were developed from the themes that emerged from this study.
Thesis (M.A. (Nursing Science) -- University of Limpopo, 2020
Keywords: Patients rights; Hospitals -- Law and legislation -- South Africa; Patients -- Civil rights